A review of eco-friendly functional road materials. (10th December 2018) - Jiang, Wei; Huang, Yue; Sha, Aimin
Graphical abstract: Highlights: Performance, applications and challenges of eco-friendly road materials is reviewed. Abundant pore structures make it possible for PAC to enable additional functions. More eco-friendly road materials will be expanded with development of science. Further studies should highlight design of road materials with multiple functions. Abstract: Extensive studies on traditional and novel engineering materials and the increasing demands by growing traffic have led to tremendous changes of the function of roads. Roads, as an important part of the human living environment, have evolved from structures that were designed and built for passing vehicles, to ecological assets with significant economic importance. In addition to structural stability and durability, functions such as noise reduction, urban heat island mitigation, de-icing and exhaust gas absorption, are also expected. This study focused on state-of-the-art research on the performance, applications and challenges of six environment-friendly functional road materials, namely the permeable asphalt concrete, noise-reducing pavement materials, low heat-absorbing pavement materials, exhaust gas-decomposing pavement materials, de-icing pavement materials, and energy harvesting pavement materials. With this study, we aim to provide references to the latest relevant literatures of the design and development of environment-friendly functional pavement, and promote innovation in materials science and pavement design principles. For this purpose, this review compiled extensive knowledge in modern road construction and related disciplines, in order to promote the development of modern pavement engineering technologies.